2013
DOI: 10.1121/1.4820808
|View full text |Cite
|
Sign up to set email alerts
|

Perceived listening effort for a tonal task with contralateral competing signals

Abstract: Perceived listening effort was assessed for a monaural irregular-rhythm detection task while competing signals were presented to the contralateral ear. When speech was the competing signal, listeners reported greater listening effort compared to either contralateral steady-state noise or no competing signal. Behavioral thresholds for irregular-rhythm detection were unaffected by competing speech, indicating that listeners compensated for this competing signal with effortful listening. These results suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
(28 reference statements)
0
7
0
1
Order By: Relevance
“…To assess effort, we used the following item from the NASA task load index: “How hard did you have to work to accomplish your level of performance?” (Hart & Staveland, ). This particular scale has previously been used in the literature to assess perceived listening effort (Bologna, Chatterjee, & Dubno, ; Mackersie & Cones, ). Below this instruction was a Likert scale with 21 increments (1 = very low , 20 = very high ).…”
Section: Methodsmentioning
confidence: 99%
“…To assess effort, we used the following item from the NASA task load index: “How hard did you have to work to accomplish your level of performance?” (Hart & Staveland, ). This particular scale has previously been used in the literature to assess perceived listening effort (Bologna, Chatterjee, & Dubno, ; Mackersie & Cones, ). Below this instruction was a Likert scale with 21 increments (1 = very low , 20 = very high ).…”
Section: Methodsmentioning
confidence: 99%
“…As noted, individuals who are hard of hearing often report that, even when they can correctly identify what is being said, listening to speech is more difficult than it was when they were younger and had better hearing. Consistent with these subjective reports, a number of researchers (McCoy et al, 2005; Nachtegaal et al, 2009; Pichora-Fuller & Singh, 2006) have reported that, in addition to reduced speech intelligibility, individuals with hearing loss often report increased effort and fatigue, particularly when listening in noise, even when changes in the listening environment do not produce changes in overall performance (Bologna, Chatterjee, & Dubno, 2013; Hick & Tharpe, 2002). …”
mentioning
confidence: 87%
“…However, clinicians and researchers have long noted that the impact of hearing loss is not solely a decline in the number of words that can be correctly recognized. Individuals with hearing loss also report increased effort and fatigue, particularly when listening in noise (Hétu, Riverin, Lalande, Getty, & St-Cyr, 1988;Hicks & Tharpe, 2002;McCoy et al, 2005;Nachtegaal et al, 2009;Pichora-Fuller, 2006), even when performance is equivalent (Bologna, Chatterjee, & Dubno, 2013;Hicks & Tharpe, 2002;McCoy et al, 2005). Though not standards of clinical care, research evaluations of interventions have employed subjective measures of effort via self-assessment scales (Ahlstrom, Horwitz, & Dubno, 2014;Cox & Alexander, 1992;Humes, Garner, Wilson, & Barlow, 2001;Sweetow & Sabes, 2006).…”
mentioning
confidence: 99%